Measurement of solid–liquid mixing quality by using a uniform design method based on image analysis - Wu, Jingyuan; Yang, Kai; Wang, Hua; Wang, Haotian; Xiao, Qingtai (Frontiers in Energy Research, 2023)
Solid-liquid mixing has been a common industrial process operation. The measurement of solid-liquid mixing quality can help to improve the efficiency of related industrial processes, but there is still a lack of an intuitive, accurate and simple measurement method. As an important indicator to evaluate the solid-liquid mixing quality, the uniformity of solid distribution is directly related to mass transfer and reaction efficiency. Therefore, it is necessary to study the solid distribution in solid-liquid system. In this work, the solid distribution of a solid-liquid system composed of glass beads-water stirred by the impeller is studied experimentally by digital image processing combined with statistical analysis. Specifically, images of solid-liquid mixing are first obtained by camera and digitally processed. The improved L2-star discrepancy is then used to quantify the uniformity of the solid-phase distribution and thus characterize the solid-liquid mixing quality. The method was compared with some known studies to prove its feasibility. Besides, the effects of various stirring factors on the solid distribution were studied and discussed by using the method. The results show that, the method proposed in this paper can measure the quality of solid-liquid mixing state more directly and can keep effective and accurate. And it was used to find the best experimental parameters in this work. This method is also simpler and cheaper than many other methods. It’s of great significance to improve the efficiency of chemical and metallurgical and other industrial processes.